Strengthening property rights for the poor - Bruce, John W. (International Food Policy Research Institute, 2004)
Who are the landed poor? That is the question asked at the beginning of this brief. The author describes the different faces of the landed poor and then take up the issue of strengthening the property rights of these groups, offering guidelines for tenure reform. Institutionalizing these tenure reforms is essential. The author concludes that strengthening the property rights of the poor is a complex project. The landed poor are a heterogeneous group who hold rights to their landed assets in diverse and complicated ways. Efforts to increase the security of their tenure need to be sensitive to the specific circumstances that characterize each case, the existing legal conditions, the strength or weakness of available financial and property registration systems, the needs of each group of stakeholders, and the possibilities of unintended consequences. Common property rights must also be protected.